Development of inactivated poliovirus vaccine from Sabin strains: A progress report. Issue 6 (November 2016) - Okayasu, Hiromasa; Sein, Carolyn; Hamidi, Ahd; Bakker, Wilfried A.M.; Sutter, Roland W.
Abstract: The Global Polio Eradication Initiative (GPEI) has seen significant progress since it began in 1988, largely due to the worldwide use of oral poliovirus vaccine (OPV). In order to achieve polio eradication the global cessation of OPV is necessary because OPV contains live attenuated poliovirus, which in rare circumstances could re-gain wild poliovirus (WPV) characteristics with potential to establish transmission. The GPEI endgame strategy for the period 2013–2018 recommends the globally synchronised sequential cessation of the Sabin strains contained in the OPV, starting with type 2 Sabin. The withdrawal of Sabin type 2 took place in April 2016, with the introduction of at least one dose of inactivated poliovirus vaccine (IPV) as a risk mitigation strategy. The introduction of IPV into 126 countries since 2013 has required a rapid scale-up of IPV production by the two manufacturers supplying the global public sector market. This scale-up has been fraught with challenges, resulting in reductions of 40–50% of initial supply commitments. Consequently, 22 countries will not be supplied until 2018, and another 23 countries will experience serious stock-outs. In the last decade repeated calls-for-action were made to the global community to invigorate their vision and investment in developing "new poliovirus vaccines" including the development of IPV from less-virulent strains, such as Sabin-IPV (S-IPV). The conventional Salk-IPV production is limited to high-income industrialized-country manufacturers due to the containment requirements (i.e., high sanitation, low force-of-poliovirus-infection, and high population immunity). The use of Sabin strains in the production of S-IPV carries a lower biosafety risk, and was determined to be suitable for production in developing countries, expanding the manufacturing base and making IPV more affordable and accessible in the long term. Significant progress in the S-IPV has been made since 2006. S-IPV is now licensed as S-IPV in Japan and as standalone S-IPV in China, demonstrating the feasibility of this vaccine. In addition, production process improvements can further reduce the cost of production. The latter are critical to the economic success of this vaccine in the global market. We summarize the progress made to date in S-IPV technology, the scientific data and economic evidence in support of S-IPV development.